Current and preservice teachers' views and beliefs regarding martial arts and the inclusion of martial arts in Australian school settings: A cross‐sectional study - Louis Burt; Nicholas Riley; Narelle Eather (Health Science Reports, 2023)
Abstract Purpose This study investigates views and beliefs of current and preservice teachers regarding martial arts (MA) and the inclusion of martial arts in schools. Methods Participants completed an anonymous, 28‐item questionnaire made available online via Qualtrics (August–November 2020). Data was analysed using SPSS software to compare mean scores by sex, and between qualified teachers and preservice teachers. Qualitative data in the form of quotes was drawn upon and used to complement the quantitative results. Results Results indicate teachers and preservice teachers view MA as a worthwhile and beneficial activity for school‐aged students, and support the inclusion of MA into school settings. Conclusion These findings may be useful to inform policy and practice in schools, and the development of teacher education programs, professional development courses, and school‐based education programs utilizing MA to meet physical education learning outcomes.